Using the K-SADS psychosis screen to identify people with early psychosis or psychosis risk syndromes. (October 2019) - Tsuji, Thomas; Phalen, Peter; Rakhshan Rouhakhtar, Pamela; Millman, Zachary; Bussell, Kristin; Thompson, Elizabeth; Demro, Caroline; Roemer, Caroline; Reeves, Gloria; Schiffman, Jason
Background: Current methods to identify people with psychosis risk involve administration of specialized tools such as the Structured Interview for Psychosis-Risk Syndromes (SIPS), but these methods have not been widely adopted. Validation of a more multipurpose assessment tool—such as the Kiddie Schedule for Affective Disorders and Schizophrenia (K-SADS)—may increase the scope of identification efforts. Methods: We assessed the correspondence between SIPS-determined clinical high risk/early psychosis (CHR/early psychosis) status and K-SADS psychosis screen (child and parent reports and their combination) in a sample of 147 help-seeking individuals aged 12–25. Detailed classification results are reported. Results: Both the child and parent interviews on the K-SADS psychosis screen were strongly predictive of CHR/early psychosis status, although parent reports contributed no significant additional information beyond child reports. Across informants, the presence of either subthreshold hallucinations or subthreshold delusions was highly suggestive of CHR/early psychosis status as determined by SIPS interview (78% (child) and 74% (parent) accuracy). Conclusions: Subthreshold scores on the two-item K-SADS psychosis screen may be good indicators of the presence or absence of early signs of psychosis. The option of using a non-specialized assessment such as the K-SADS as a staged approach to assess for CHR/early psychosis status could increase rates of early psychosis screening and treatment.